Bortezomib, melphalan, and prednisone with or without daratumumab in transplant-ineligible patients with newly diagnosed multiple myeloma (ALCYONE): final analysis of an open-label, randomised, multicentre, phase 3 trial - Mateos, Maria-Victoria; San-Miguel, Jesus; Cavo, Michele; Suzuki, Kenshi; Jakubowiak, Andrzej; Knop, Stefan; Doyen, Chantal; Lucio, Paulo; Nagy, Zsolt; Pour, Ludek; Grosicki, Sebastian; Crepaldi, Andre; et al. (The Lancet. Oncology, 2025)
BACKGROUND: In the phase 3 ALCYONE study, the addition of daratumumab to bortezomib, melphalan, and prednisone (D-VMP) significantly improved outcomes in transplant-ineligible patients with newly diagnosed multiple myeloma. Here, we present results from the final analysis of ALCYONE. METHODS: ALCYONE was an international, multicentre, randomised, open-label, active-controlled, phase 3 trial in adults aged 18 years or older with newly diagnosed multiple myeloma who were ineligible for high-dose chemotherapy with autologous stem-cell transplantation, because of their age (≥65 years) or presence of substantial comorbidities, and had an Eastern Cooperative Oncology Group performance status of 0-2. Patients were enrolled between Feb 9, 2015, and July 14, 2016, and were randomly assigned (1:1) by randomly permuted blocks using an interactive web-based randomisation system to receive bortezomib, melphalan, and prednisone (VMP) alone or D-VMP, with randomisation stratified by International Staging System disease stage, geographical region, and age. Patients received up to nine 6-week cycles of subcutaneous bortezomib (1·3 mg/m2 of body surface area, twice per week on weeks 1, 2, 4, and 5 of cycle 1 and once weekly on weeks 1, 2, 4, and 5 of cycles 2-9), oral melphalan (9 mg/m2, once daily on days 1-4 of each cycle), and oral prednisone (60 mg/m2, once daily on days 1-4 of each cycle). Patients in the D-VMP group also received intravenous daratumumab at a dose of 16 mg/kg once weekly during cycle 1, once every 3 weeks in cycles 2-9, and once every 4 weeks thereafter until disease progression, unacceptably toxicity, or the end of study. The primary endpoint, progression-free survival, has been previously reported. The ALCYONE study has completed; presented here are final analyses for selected secondary endpoints related to overall survival, depth of response, subsequent therapy, and safety. The intention-to-treat population was the primary analysis population (including for overall survival), defined as all patients who were randomly assigned to study treatment. The safety population, consisting of patients who received any dose of study treatment, was used in safety analyses. This trial is registered with ClinicalTrials.gov, NCT02195479. FINDINGS: In total, 706 patients were enrolled and randomly assigned to receive D-VMP (n=350) or VMP (n=356). Baseline characteristics were balanced between the two treatment groups; most participants were female (379 [54%] of 706 patients) and White (601 [85%] of 706 patients). At a median follow-up of 86·7 months (IQR 28·5-85·2), median overall survival was 83·0 months (95% CI 72·5-not estimable) with D-VMP versus 53·6 months (46·3-60·9) with VMP (hazard ratio [HR] 0·65 [95% CI 0·53-0·80]; p<0·0001). The most common grade 3 or 4 treatment-emergent adverse events were neutropenia (140 [40%] of 346 patients in the D-VMP group vs 138 [39%] of 354 patients in the VMP group), thrombocytopenia (120 [35%] vs 134 [38%]), and anaemia (63 [18%] vs 70 [20%]). Serious treatment-related adverse events occurred in 74 (21%) of 346 patients in the D-VMP group and 56 (16%) of 354 patients in the VMP group. Deaths due to treatment-related adverse events occurred in five (1%) of 346 patients in the D-VMP group (pneumonia, acute myocardial infarction, neuroendocrine tumour, tumour lysis syndrome, and acute respiratory failure) and three (1%) of 354 patients in the VMP group (acute myeloid leukaemia, pulmonary embolism, and bacterial pneumonia). INTERPRETATION: With more than 7 years of follow-up, D-VMP continued to elicit clinical benefits in transplant-ineligible patients with newly diagnosed multiple myeloma, supporting the efficacy and safety of frontline daratumumab-based therapy in this patient population. FUNDING: Janssen Research & Development.
Keywords: Humans; lidé středního věku; Multiple Myeloma; Female; Prednisone; Aged; Antibodies, Monoclonal; protokoly protinádorové kombinované chemoterapie; melfalan; senioři; lidé; doba přežití bez progrese choroby; mnohočetný myelom; bortezomib; prednison; Melphalan; ženské pohlaví; Male; Middle Aged; Bortezomib; Antineoplastic Combined Chemotherapy Protocols; Aged, 80 and over; monoklonální protilátky; senioři nad 80 let; Progression-Free Survival; mužské pohlaví